System Approach To Labor Productivity Management In Modern Crisis Conditions - Geseleva, N.; Proniuk, G. V. (MIND, 2020)
The article is devoted to the development of a system approach for managing labor productivity in a company especially in crisis conditions. A company is considered as a complicated system with a certain external environment, patterns of development and internal structure. The main component of the internal structure is the personnel of the company, which the authors regard as a dissipative system, and each employee as an open system that exchanges energy and entropy with the environment. The article suggests the entropy factors of labor productivity. Based on the equilibrium state of an employee as a system, it has been shown that labor productivity can be enhanced by the motivational factor of self-improvement for each member of the work community
Keywords: labor productivity; equilibrium state; bifurcation points